TYPOLOGY OF HABITAT NEPENTHES ARISTOLOCHIOIDES IN KERINCI SEBLAT NATIONAL PARK - Mandala, Bakti; Zuhud, Ervizal A.M; Rahman, Dede Aulia (Department of Forest Resources Conservation and Ecotourism - IPB University, 2023)
Nepenthes aristolochioides is an endemic species found in Indonesia. This species has a narrow ecological distribution on Mount Tujuh, in the forest area of Kerinci Seblat National Park (TNKS), Kerinci Regency, Jambi Province. Nepenthes aristolochioides is a rare and critically endangered species of Nepenthes. Unfortunately, the study of environmental factors that influence its existence has not been widely studied. Therefore, a prediction model for the distribution of N.aristolochioides is needed as a solution for managing its habitat. This study aims to make a prediction map of the habitat of N.aristolochioides in Kerinci Seblat National Park. Characteristics of the environmental factors of the N.aristolochiodes habitat that play an essential role in habitat suitability are the variables BIO19 (Precipitation of Coldest Quarter), BIO1 (Annual Mean Temperature), BIO13 (Precipitation of Wettest Month), DEM (Digital Evaluation Model). Prediction of the distribution of N.aristolochiodes habitat with moderate habitat suitability of 10.523 ha, while with a high suitability level, is 4.176 ha. Habitats with a high level of conformity are spread over two main administrative areas, namely, Gunung Tujuh Sector, Gunung Kerinci Sector Key words: Habitat distribution, Maximum Entropy, Nepenthes aristolochioides